KINERJA KUALITAS PELAYANAN DAN PENGARUHNYA TERHADAP KEPUASAN PELANGGAN BENGKEL JM MOTOR BANDUNG BARAT - Suharyanto Suharyanto (Spektrum Industri, 2018)
The motorcycle industry in Indonesia have been growing fast in recent years and it is synergic with the motorcycle demanded by the people. The motor cyles service station increase simultaneously with motorcycle population. The motorcyles service station that exist in Kelurahan Tanimulya, Kecamatan Ngamprah Kabupaten Bandung  Barat more than ten units including JM Motor. The impacts and consequencies caused by this condition are:  the competitive  climate and the owners  have to defense, struggle and improve their businesses. These aims can be reached through service quality improvement and customer satisfaction. The JM Motor Service station   serves the many kinds and brands of  motorcyles such as general check-up, oil refilling, engine tune-up and overhauls, lamps and tires replacement and others including sales of spareparts. This research  provides to know the service quality aspects (reliability, responsiveness, assurance, empathy and tangibles) that have been giving and effects to the  customer satisfaction.   The 40 questionnaires  collected by using incidental sampling method to get the  service quality and customer satisfaction data and interviews to get the managerial data.   The result shows that the services quality aspects effected low rated with coefficient of determination  R2= 32,6% ; it means that services quality effected to customers satisfaction 32,6% and 67,4% caused by other factors.  The regression equation  constructed is CS= 3.482 + 0.143SQ, where CS= customers satisfaction and SQ = services quality. It means that services quality gives rather low impact to customers satisfaction of JM Motor Service station.